Big Green And Careful: How major California Newspapers Covered Two Ballot Initiatives in the 1990 General Election - Gary A. Beall; James H. Hayes (Journal of Applied Communications, 1992)
Big Green And Careful: How major California Newspapers Covered Two Ballot Initiatives in the 1990 General Election